2016
DOI: 10.1016/j.aogh.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Care in Republic of Macedonia: Challenges and Opportunities

Abstract: A new National eHealth System allows for better identification and monitoring of citizens with diabetes. However, the rapidly growing expense of insulin in the past has been unsustainable. The potential exists for a stronger role for lifestyle interventions in prevention and treatment of T2D. Significant changes in dietary patterns parallel the rise in diabetes prevalence and are likely a leading cause of diabetes and its complications. Research in RoM is needed to determine the impact and acceptability of die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 24 publications
(19 reference statements)
0
29
0
Order By: Relevance
“…This system fulfils all requirements of the international standards and covers studyrelevant information for all citizens of the Republic of Macedonia [23,24]. Patients recruited for the current study have been identified as postmenopausal females with past history of menopause defined as one year after last menstrual period without bleeding, who have developed breast cancer after this time (in menopause), therefore, being postmenopausal breast cancer patients.…”
Section: Breast Cancer Patient Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…This system fulfils all requirements of the international standards and covers studyrelevant information for all citizens of the Republic of Macedonia [23,24]. Patients recruited for the current study have been identified as postmenopausal females with past history of menopause defined as one year after last menstrual period without bleeding, who have developed breast cancer after this time (in menopause), therefore, being postmenopausal breast cancer patients.…”
Section: Breast Cancer Patient Cohortmentioning
confidence: 99%
“…The age difference was evaluated as statistically non-significant. Postmenopausal breast cancer group demonstrated in average the BMI = 26 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Fifty percent of this group were overweight persons and 20% were diagnosed with diabetes type 2.…”
Section: General Statisticsmentioning
confidence: 99%
“…A considerable increase in calories per capita per day, a sedentary lifestyle, transition society-related stress, and a high national smoking rate are the main reasons for the dramatic rise of type 2 diabetes in the past 25 years [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, public awareness programs were developed highlighting the importance of nutrition, physical activity and smoking cessation, and diabetesspecific patient data were integrated into the National eHealth System [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation